A scoping review and a taxonomy of the use of motion-based technology centered on the end user. A special focus on elderly health - Bossavit, Benoit; Fernández-Leiva, Antonio José (Springer, 2023)
Motion-based technology (MBT) has been applied in the last decades with enormous success in a high number of applications. Its use continues growing and is specially interesting in the health area. Nowadays, its employment is being more and more specialised with respect to the profile of the end user (i.e., child, adolescent/teenager, adult or elderly). This paper first reviews the use of MBT centered in the end user from a global perspective. It also proposes a taxonomy that allows cataloguing the MBT employment directed to the end user. Then, from these results, the paper centers the review on the MBT application aiming to improve the health of elderly. The results highlighted in this paper can help to a better understanding of MBT, especially when it is applied thinking in elderly as the end users.
Keywords: Ancianos - Actividad; Ejercicio físico; Motion-based technology; Elderly; Taxonomy; Digital games; Health